The edge of words : God and the habits of language - Williams, Rowan, 1950- (2014)
The Edge of Words is Rowan Williams' first book since standing down as Archbishop of Canterbury. Invited to give the prestigious 2014 Gifford Lectures, Dr Williams has produced a scholarly but eminently accessible account of the possibilities of speaking about God -- taking as his point of departure the project of natural theology. Dr Williams enters into dialogue with thinkers as diverse as Augustine and Simone Weil and authors such as Joyce, Hardy, Burgess and Hoban in what is a compelling essay about the possibility of language about God --
A future for 'natural theology'? -- Can we say what we like? Language, freedom and determinism -- Speech and time: the unfinishable business of language -- Intelligent bodies: language as material practice -- Excessive speech: language in extreme situations -- Saying the unsayable: where silence happens.
"A Continuum book"--Title page verso.
Includes bibliographical references and index.
Keywords: God (Christianity); Language and languages -- Religious aspects -- Christianity